External and internal factors influencing impulse buying behaviour of Malaysian credit card owners in reference to gender - Harun, Amran; Lee, Ik Lin Ellen; Mohd Kassim, Abdul Wahid; Tahajuddin, Sulaiman; Shamsudin, Abdul Shukor (Institute of Advanced Scientific Research, 2018)
Malaysians perceived shopping as a leisure activity, however studies on impulse behaviour in Malaysia is limited and more studies are needed. Hence, this study aims to understand the factors influencing impulse buying behaviour of consumers who own a credit card. The objectives of this study are threefold: 1) to examine the external and internal factors influencing impulse buying behaviour, 2) to investigate the moderating effect of gender on the factors and impulse buying behaviour, and 3) to understand impulse buying behaviour of the male and female consumers. The external factors are the usage of credit card, promotional approaches, and window display; the internal factors are consumer mood (good and bad) and consumer impulse buying tendency. A total of 203 credit card owners participated in this study and data was obtained through the questionnaire distribution. The results indicated only promotional approaches, window display, and consumer bad mood were found significantly related to impulse buying behaviour. Surprisingly, there was no moderating effect of gender and no differences were found between male and female consumers impulse buying behaviour. Therefore, the marketing efforts for products that fall into impulse buying behaviour category should not be segregated according to gender. Marketers should emphasize more on promotional efforts and attractive window display within their retail store to attract more consumers to buy impulsively.